2016
DOI: 10.1007/s12565-016-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system in vertebrates: phylogenetic view of structure and function

Abstract: Renin substrate, biological renin activity, and/or renin-secreting cells in kidneys evolved at an early stage of vertebrate phylogeny. Angiotensin (Ang) I and II molecules have been identified biochemically in representative species of all vertebrate classes, although variation occurs in amino acids at positions 1, 5, and 9 of Ang I. Variations have also evolved in amino acid positions 3 and 4 in some cartilaginous fish. Angiotensin receptors, AT and AT homologues, have been identified molecularly or character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 226 publications
0
38
0
Order By: Relevance
“…Although non-mammalian vertebrate kidneys do not possess JG or have rudimentary JG, there are functional baroreceptor mechanisms in fish [e.g. toadfish (Opsanus tau) (Nishimura et al, 1979), reptiles (turtle, Pseudemys scripta) (Stephens and Creekmore, 1984) and birds (Nishimura, 2017)]. Indeed, in common slider turtles (Pseudemys scripta), barostatic mechanisms were responsible for renin release following hypotension caused by hemorrhage (Stephens and Creekmore, 1984).…”
Section: Raas and Lingual Glandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although non-mammalian vertebrate kidneys do not possess JG or have rudimentary JG, there are functional baroreceptor mechanisms in fish [e.g. toadfish (Opsanus tau) (Nishimura et al, 1979), reptiles (turtle, Pseudemys scripta) (Stephens and Creekmore, 1984) and birds (Nishimura, 2017)]. Indeed, in common slider turtles (Pseudemys scripta), barostatic mechanisms were responsible for renin release following hypotension caused by hemorrhage (Stephens and Creekmore, 1984).…”
Section: Raas and Lingual Glandsmentioning
confidence: 99%
“…Thus, these findings correspond well with results from the present study in which ALDO levels were not significantly different in SW alligators compared with FW alligators after 5 weeks. ALDO secretion in vertebrates is regulated by ANG II in addition to the adrenocorticotropic hormone (ACTH) and plasma K + (Nishimura, 2017). It has previously been demonstrated that ALDO and CORT secretions in alligators are stimulated by ACTH, which is released from the pituitary gland (Lance and Lauren, 1984;Morici, 1996).…”
Section: Raas and Lingual Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The renin-angiotensin system (RAS) is classically described as an important endocrine system that regulates blood pressure and electrolyte balance. Studies have demonstrated that RAS may be involved in numerous pathophysiological processes, such as maintaining blood pressure/blood volume homeostasis and ion-fluid balance, phylogenetic advancement, growth promotion and angiogenesis, ontogeny and phylogeny (6). RAS is also involved in several cancers, including glioblastoma multiform (7), and bladder (8) and renal (9) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the renin-angiotensin cascade is initiated by the release of renin from the juxtaglomerular cells in the renal afferent arteriole. Renin is released by hypovolemia and subsequent decreases in perfusion pressure at the arteriole ( Kobayashi and Takei, 1996 ; Nishimura, 2017 ). The principal action of the active principle, Ang II, is to restore blood volume by retaining NaCl and water.…”
Section: Amphibious Mudskipper As a Unique Model For Studying Osmoregmentioning
confidence: 99%